Systematic characterization and functional analysis of trans-prenyltransferases in Curcuma wenyujin - Wang, Qian; Su, Yi; Ye, Tingyu; Wu, Shiyi; Liu, Huan; Sun, Jingwen; Yin, Xiu; Hu, Tianyuan; Ma, Xiaoxia; Zhao, Shujuan; Xu, Xinde; Yin, Xiaopu; et al. (Frontiers in Plant Science, 2025)
IntroductionCurcuma wenyujin (Zingiberaceae), a medicinally significant species within the Curcuma genus, is highly regarded in traditional Chinese medicine for its rich terpenoid constituents. These specialized metabolites serve as the principal bioactive components underpinning the plant's therapeutic effects. As key enzymes in terpenoid biosynthesis, trans-prenyltransferases (trans-PTs) play crucial roles in regulating metabolic flux.MethodsTrans-PTs in C. wenyujin were identified through a comprehensive transcriptome-wide analysis. The identified CwPTs were classified by constructing a phylogenetic tree. Their transcriptional responses to abscisic acid (ABA), methyl jasmonate (MeJA), and gibberellic acid (GA) were assessed. The catalytic functions of CwFPS1 and CwGGPS1 were characterized through in vitro enzyme assays and heterologous expression in Escherichia coli.ResultsEight trans-CwPTs were identified in C. wenyujin. Among them, five CwPTs function as geranylgeranyl pyrophosphate synthases (GGPS), two as solanesyl pyrophosphate synthases (SPS), and one as farnesyl pyrophosphate synthase (FPS). Expression profile assay showed more significant changes in the transcription levels of CwPTs in response to ABA and MeJA than to GA. CwFPS1 catalyzed the biosynthesis of farnesyl pyrophosphate (FPP) through the sequential condensation of dimethylallyl pyrophosphate (DMAPP) and isopentenyl pyrophosphate (IPP), as well as geranyl pyrophosphate (GPP) and IPP. CwGGPS1 catalyzed the condensation of GPP or FPP with IPP to generate geranylgeranyl pyrophosphate (GGPP) in vitro. Furthermore, these functions were confirmed in Escherichia coli.DiscussionOur research establishes a molecular foundation for understanding terpenoid biosynthesis in C. wenyujin. Future sequencing of the C. wenyujin genome will facilitate the development of additional CwPTs.